An Analysis Method of the Temporal Instability and the Non-Uniformity of the Chip-On-Board Light Emitting Diodes Solar Simulator - Watjanatepin, Napat; Kiatsookkanatorn, Paiboon (International Journal of Engineering and Technology, 2018)
The purpose of this paper is to test the temporal instability of irradiance and the non-uniformity on the test plane of the COB-LEDs based solar simulator. This study followed the process according to the IEC 60904-9 standard. The 3Ã—6 arrays of COB-LEDs consume the total power of about 900 watts and are installed on the aluminium profile heat sink. The illumination area is about 448 cm2. The switching power supply was used to supply power to the LEDs. The research tool is the irradiance instruments that were calibrated by the secondary standard Pyranometer. The results found that the COB-LEDs solar simulator met the standard IEC 60904-9 in Class -CB. The results confirmed that this innovative idea can be applied to make the best LEDs based solar simulator. For future works, the author planned to improve the non-uniformity and temporal stability to meet the A Class.Â Â